SimCoach Evaluation A Virtual Human Intervention to Encourage Service-Member Help-Seeking for Posttraumatic Stress Disorder and Depression - Meeker, Daniella (RAND Corporation, 2015)
This report describes RAND Corporation researchers' assessment of SimCoach, a computer program featuring a virtual human that speaks and gestures in a video game-like interface, designed to encourage service members, especially those with signs or symptoms of posttraumatic stress disorder or depression, to seek help for psychological health concerns.